Zerumbone Modulates α2A-Adrenergic, TRPV1, and NMDA NR2B Receptors Plasticity in CCI-Induced Neuropathic Pain In Vivo and LPS-Induced SH-SY5Y Neuroblastoma In Vitro Models - Chia, Jasmine Siew Min; Izham, Noor Aishah Mohammed; Farouk, Ahmad Akira Omar; Sulaiman, Mohd Roslan; Mustafa, Sanam; Hutchinson, Mark R.; Perimal, Enoch Kumar (Frontiers in Pharmacology, 2020)
Zerumbone has shown great potential in various pathophysiological models of diseases, particularly in neuropathic pain conditions. Further understanding the mechanisms of action is important to develope zerumbone as a potential anti-nociceptive agent. Numerous receptors and pathways function to inhibit, and modulate transmission of pain signals. Previously, we demonstrated involvement of the serotonergic system in zerumbone’s anti-neuropathic effects. The present study was conducted to determine zerumbone’s modulatory potential involving noradrenergic, TRPV1 and NMDA receptors in CCI-induced in vivo and LPS-induced SH-SY5Y in vitro neuroinflammatory models. von Frey filament and Hargreaves plantar tests were used to assess allodynia and hyperalgesia in the chronic constriction injury-induced neuropathic pain mouse model. Involvement of specific adrenoceptors were investigated using antagonists – prazosin (α1-adrenoceptor antagonist), idazoxan (α2-adrenoceptor antagonist), metoprolol (β1-adrenoceptor antagonist), ICI 118,551 (β2-adrenoceptor antagonist) and SR 59230 A (β3-adrenoceptor antagonist), co-administered with zerumbone (10 mg/kg). Involvement of excitatory receptors; TRPV and NMDA, were conducted using antagonists capsazepine (TRPV antagonist) and memantine (NMDA antagonist). Western blot was conducted to investigate the effect of zerumbone on the expression of α2A-adrenoceptor, TRPV1 and NMDA NR2B receptors in CCI-induced whole brain samples of mice as well as in LPS-induced SH-SY5Y neuroblastoma cells. Pre-treatment with α1- and α2-adrenoceptor antagonists significantly attenuated both anti-allodynic and anti-hyperalgesic effects of zerumbone. For β-adrenoceptors, only β2-adrenoceptor antagonist significantly reversed the anti-allodynic and anti-hyperalgesic effects of zerumbone. β1-adrenoceptor antagonist only reversed the anti-allodynic effect of zerumbone. The anti-allodynic and anti-hyperalgesic effects of zerumbone were both absent when TRPV and NMDA receptors were antagonized in both nociceptive assays. Zerumbone treatment markedly decreased the expression of α2A-adrenoceptor, while an up-regulation was observed of NMDA NR2B receptors. Expression of TRPV1 receptors however did not significantly change. The in vitro study, representing a peripheral model, demonstrated the reduction of both NMDA NR2B and TRPV1 receptors while significantly increasing α2A-adrenoceptor expression in contrast to the brain samples. Our current findings suggest that the α1-, α2-, β1- and β2-adrenoceptors, TRPV1 and NMDA NR2B are essential for the anti-allodynic and antihyperalgesic effects of zerumbone. Alternatively, we demonstrated the plasticity of these receptors through their response to zerumbone’s administration.